Association of breast milk microbiota and metabolites with neonatal jaundice - Liu, TianYu; Yuan, Yanhan; Wei, Jinying; Chen, Jiayi; Zhang, Feng; Chen, Juanjuan; Zhang, Jinping (Frontiers in Pediatrics, 2025)
BackgroundBreast milk is the primary source of nutrition during early life, and existing research indicates that the development of jaundice in breastfed newborns may be linked to specific nutrients or bioactive substances present in breast milk. However, the association between the microbiota and small-molecule metabolites in breast milk and the development of neonatal jaundice remains unproven. This study aimed to investigate the development of jaundice in breastfed neonates in relation to breast milk microbiota and metabolites.MethodsBased on the conditions of exclusive breastfeeding, we selected healthy newborns without significant jaundice and their mothers on day 4 (96–120 h after birth) as the healthy control group, and jaundiced newborns and their mothers as the jaundice group. Breast milk samples were collected from mothers in both groups on postnatal day 4 and analyzed for microbiota and small-molecule metabolites using 16S rRNA gene sequencing and an liquid chromatography-tandem mass spectrometry techniques.ResultsA total of 104 mother-child pairs were included in the study, of which 51 pairs were in the healthy control group and the other 53 pairs were in the jaundice group. Our results demonstrated that there was no significant difference between the species composition and diversity of the breast milk flora in the healthy control and jaundice groups. At the genus level, the abundance of Lactobacillus, Ackermannia, and Bifidobacterium was significantly higher in the breast milk of the healthy control group than in the jaundice group. Metabolomics analysis revealed a total of 27 significantly different metabolites between the two groups. Notably, breast milk from the healthy control group had elevated levels of 24 metabolites, predominantly lipids family, including sphingolipids, phospholipids, and fatty acid derivatives.ConclusionThis study suggests that there is a link between the development of neonatal jaundice and breast milk microbiota and metabolites. Breast milk from mothers of healthy newborns contains higher levels of beneficial bacteria and lipid family compared to mothers of newborns with jaundice. This study offers new insights into the relationship between breastfeeding and neonatal jaundice.